Fluoro analogs of bioactive oxy-sterols: Synthesis of an EBI2 agonist with enhanced metabolic stability. Issue 20 (15th October 2016) - Deng, Xiaohu; Sun, Siquan; Wu, Jiejun; Kuei, Chester; Joseph, Victory; Liu, Changlu; Mani, Neelakandha S.
Graphical abstract: Synthesis of several 7-hydroxy oxysterols and their potential roles as signaling molecules in the innate and adaptive immune responses is discussed. Discovery of a new, fluorinated, synthetic analog of the 7α, 25-dihydroxycholesterol—the endogenous ligand of GPR 183 (EBI2), a G-protein coupled receptor highly expressed upon Epstein–Barr virus infection is described. Fluoro oxysterol12 showed good metabolic stability while maintaining excellent EBI2 agonist activity. Abstract: Synthesis of several 7-hydroxy oxysterols and their potential roles as signaling molecules in the innate and adaptive immune responses is discussed. Discovery of a new, fluorinated, synthetic analog of the 7α, 25-dihydroxycholesterol—the endogenous ligand of GPR 183 (EBI2), a G-protein coupled receptor highly expressed upon Epstein–Barr virus infection is described. Fluoro oxysterol12 showed good metabolic stability while maintaining excellent EBI2 agonist activity.